EFEKTIVITAS BABY MASSAGE TERHADAP FREKUENSI DAN DURASI MENYUSU PADA BAYI USIA 0-6 BULAN - Ayuk Widiani (STIKES ADVAITA MEDIKA TABANAN, 2023)
Breastmilk is a source of nutrition that is ideal because of its balanced composition and is the most perfect for baby's needs, both in quality and quantity. The scope of exclusive breastfeeding is indeed increasing every year but is still below target. To increase the achievement of exclusive breastfeeding requires a stimulation of a massage baby. One of the basic mechanisms of baby massage is the activity of the vagus nerve increases the volume of milk and better absorption so that the baby is hungry quickly and will suckle more often to his mother. The purpose of this study was to determine the effectiveness of baby massage on the frequency and duration of breastfeeding infants aged 0-6 months. The design of this study is Quasi Experiment with Pretest-Posttest Control Group Design. The sample of this study totaled 30 respondents (15 babies as a control group and 15 babies as treatment groups) with purposive sampling techniques. The data collection tool used is a standard operating procedures of Baby Massage, Observation Forms of Frequency and Breastfeeding Duration of Babies Age 0-6 Months. Bivariate data analysis using the Mann Whitney test and T-test independent test. The results of the study found that there was a significant difference in frequency and duration of breastfeeding in infants aged 0-6 months in treatment group and control group (P = 0.001 and P = 0.016). This proves the baby massage is very useful in helping exclusive breastfeeding achievement if done routinely.